C62.22.1-2024 - IEEE Guide for Connection of Surge Arresters to Protect Insulated Shielded Electric Power Cable Systems Up to 46 kV (IEEE, 2025)
Surge arrester installation methods at distribution cable terminal poles to minimize the total impressed transient voltage on medium-voltage distribution cables are suggested in this guide. Grounding electrode techniques, pole ground values, and system ground grid values are not addressed or considered in this document.
Keywords: Voltage regulators.